MULTI-SYSTEM INFLAMMATORY SYNDROME IN PATIENTS ADMITTED AT NICU OF A TERTIARY CARE HOSPITAL - ZAHRA, M; NIAZI, S; CHOUDHRY, S; KHAN, EA (Biological and Clinical Sciences Research Journal, 2024)
Multi-inflammatory syndrome in neonates (MIS-N) associated with COVID-19 is an emerging concern in neonatal intensive care units (NICUs). Understanding its clinical spectrum and outcomes is crucial for developing management strategies and improving neonatal care. Objective: To explore the clinical spectrum, associated laboratory markers, and outcomes of neonates diagnosed with MIS-N and COVID-19 admitted to the NICU. Methods: This case series was conducted at the NICU of Shifa International Hospital, Islamabad, from January 2023 to June 2023. It included 47 infants diagnosed with COVID-19 who developed MIS-N. Data collected encompassed clinical presentations, laboratory markers, treatments administered in the ICU, and clinical outcomes. Descriptive statistics were used to analyze the data, focusing on symptoms, treatment efficacy, and complications. Results: The neonates had a mean age of 20.65 ± 16.60 days and a mean gestational age of 36.40 ± 2.62 weeks. Elevated inflammatory markers were noted, with D-Dimers elevated in 46.8%, serum ferritin in 66%, and C-reactive protein (CRP) in 48.9% of patients. The most common symptoms included respiratory distress (74.5%), poor feeding (38.3%), and fever (29.8%). Significant findings included pulmonary hypertension in 27.7% of the patients, patent ductus arteriosus in 23.4%, and other cardiovascular anomalies. Complications such as sepsis (70.2%), oxygen dependency (21.3%), and renal failure (29.8%) were prevalent. The mortality rate was 12.8%. Conclusion: MIS-N presents a severe threat to neonates with COVID-19, demonstrating high rates of serious complications and a notable mortality rate. Echocardiography is essential for early detection of cardiac dysfunctions. These findings underscore the urgent need for specific guidelines for the early recognition and management of MIS-N in neonates.